2018
DOI: 10.1002/nau.23836
|View full text |Cite
|
Sign up to set email alerts
|

Uroflow measurement combined with electromyography testing of the pelvic floor in healthy children

Abstract: Aims: To investigate if the standard protocol for uroflowmetry, recommended by the International Children's Continence Society, remains accurate when integrating EMG measurement by means of superficial electrodes. Methods: A cross-sectional study was conducted including healthy children. Group A performed two direct repetitions of uroflowmetry in combination with electromyography (uroflow/EMG). Group B performed a preceding measurement of isolated uroflowmetry, followed by two randomized measurements of uroflo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 23 publications
(43 reference statements)
0
6
0
Order By: Relevance
“…Although the LUTDSS of those patients was higher than 8.5, their UF-EMG findings were similar with the control group. Samijn et al (12) reported 50-60% of children with LUTS void on the bell-shaped curve and suggested that initiation to the procedure with a UF alone and followed by a measurement of UF with EMG. Similar with this study, we have found the rate of Grade 0 and Grade 1 which were bell shaped curve in 54% of the patient.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the LUTDSS of those patients was higher than 8.5, their UF-EMG findings were similar with the control group. Samijn et al (12) reported 50-60% of children with LUTS void on the bell-shaped curve and suggested that initiation to the procedure with a UF alone and followed by a measurement of UF with EMG. Similar with this study, we have found the rate of Grade 0 and Grade 1 which were bell shaped curve in 54% of the patient.…”
Section: Resultsmentioning
confidence: 99%
“…LUTDSS is a diagnostic tool for the diagnosis of LUTD in children with a score of 8.5 or greater had voiding abnormalities, with 90% sensitivity and 90% specifity (10). The questionnaire was composed of the following items: daytime urinary incontinance (Q1,2), nighttime urinary incontinance (Q3,4), frequency (Q5), voiding habits as strain, pain during voiding, intermittency (Q6,7,8,9), bladder habits as urgency and urge incontinance (Q10, 11,12), constipation (Q13) and quality of life. UF-EMG studies were performed by the expert nurse (MMS 5000, Medical measurement system 5000, USA) in our urodinamy study center.…”
Section: Methodsmentioning
confidence: 99%
“…Although a repeated UF was conducted when possible, there is still a possibility that the patching of EMG itself affected EMG relaxation and urination by causing discomfort and anxiety to the patients. 14…”
Section: Discussionmentioning
confidence: 99%
“…Though the examiner performed inspections, simultaneous audio monitoring to confirm the absence of motor activity during voiding was not performed to assess the EMG artifact. Although a repeated UF was conducted when possible, there is still a possibility that the patching of EMG itself affected EMG relaxation and urination by causing discomfort and anxiety to the patients 14 …”
Section: Discussionmentioning
confidence: 99%
“…Uroflowmetry was reported to be a diagnostic tool which is comfortable for patients, relatively inexpensive, and time-efficient procedure which shows the natural voiding pattern in children (6)(7)(8) . It gives the results of voiding speed, voided volume, and voiding curve (9) . Uroflowmetry has a high sensitivity but low specificity, which might interfere with the diagnosis (10) .…”
Section: Introductionmentioning
confidence: 99%